Advancing Scientific Literacy through Digital Learning Media and Learning Management Systems in Online Learning: A Systematic Review - wersi handayani; Mohammad Qais Rezvani; Amel Zulfukar Hassan Adlan (Journal of Sustainable Educational Technology and Innovation, 2026)
Background: The rapid development of digital technology has transformed online learning, making digital learning media and Learning Management Systems (LMS) important components in supporting scientific literacy. However, previous studies have reported fragmented findings regarding the effectiveness of integrating digital learning media and LMS in enhancing students' scientific literacy.Aims: This study aims to systematically review the current literature on the integration of digital learning media and Learning Management Systems in online learning and to identify research trends, implementation strategies, and their contributions to improving scientific literacy.Methods: This study employed a Systematic Literature Review (SLR) following the PRISMAguidelines. Relevant publications from 2020–2026 were retrieved from the Scopus database using keywords related to scientific literacy, online learning, digital learning, and technology/media/platform. The retrieved data were refined using OpenRefine, analyzed bibliometrically through Biblioshiny and  VOSviewer, and synthesized using Elicit AI. After applying the inclusion and exclusion criteria, eight eligible articles were included in the final review.Results: The review indicates that integrating digital learning media with LMS positively contributes to scientific literacy by improving conceptual understanding, learning outcomes, scientific data interpretation, and student engagement in online learning. Most studies employed Research and Development (50%), followed by quantitative (25%), qualitative (12.5%), and mixed-methods (12.5%) approaches.Conclusion: Integrating digital learning media and Learning Management Systems has significant potential to enhance scientific literacy in online learning. Future research should expand implementation across diverse educational contexts and strengthen methodological rigor to support sustainable digital learning innovations.